Elevated Second Trimester Alpha-Fetoprotein Increases the Risk of Placenta Accreta - Fengge Wang; Dongmei Man; Shiguo Liu (Clinical and Experimental Obstetrics & Gynecology)
Background: Placenta previa-accreta constitutes an increasing clinical problem, whose diagnosis remains challenging in obstetrics. The current work aimed to assess whether second-trimester serum alpha-fetoprotein (AFP) amounts are altered in pregnant women with placenta previa-accreta versus control values. Methods: A retrospective chart review was performed for 504 pregnant women treated between 1 January 2016 and 28 February 2021. This cohort included 105 placenta previa-accreta and 122 placenta previa control cases, as well as 277 body mass index (BMI)-matched individuals with healthy pregnancy. The multiple of the median (MoM) for AFP was obtained from clinical records. Results: Markedly elevated MoM for AFP was detected in the placenta previa-accreta group compared with the placenta previa control and healthy pregnant control groups (both p < 0.001). Serum AFP levels had a significant positive association with placenta accreta after adjustment for age, BMI, and gestational week at blood collection (β = 0.60; 95% confidence interval [95% CI]: 0.52, 0.68; p < 0.001). In addition, previous cesarean delivery history (β = 3.41; 95% CI: 2.18, 5.34; p < 0.001) also had a significant association with placenta accreta. Conclusions: Elevated second-trimester serum AFP had a positive association with placenta accreta. Such finding suggests a potential role for AFP in detecting pregnancies at high-risk of placenta accreta. This second-trimester biomarker of AFP may help classify women into the high- and low-risk groups for placenta accreta. In addition, we have validated a previous history of cesarean section as a risk factor for accreta in patients with placenta previa.